Factors influencing the tourist’s visit to kandalama tank: a study using individual travel cost method - Lakmali, C.; Sooriyakumar, K.; Sarujan, S. (University of Jaffna, 2017)
Tourism is considered as one of the largest and fastest developing sectors of the world. The recreational and ecological benefits of reserving national parks and improving water quality in lakes and tanks have been widely acknowledged. Kandalama tank in Dambulla, Sri Lanka is considered as the best reservoir in Sri Lanka for various reasons. It irrigates the farmland, supplies drinking water, supports fishery and provides a venue for recreation and relaxation. Kandalama tank has high potential to attract more tourists, however, due to limited infrastructure facilities and services provided to the local tourists, higher fee for services such as ballooning, inadequate measures to control environmental pollution and unethical activities, it could not achieve its potential level. The objective of this study was to identify factors affecting tourist’s visit to Kandalama tank. For this study, data were collected randomly from 130 visitors, using structured questionnaire. Using these data, a travel cost model for tourists’ demand for Kandalama tank was developed using Ordinary Least Square (OLS) method. Results of this study indicated that those who visit other place in their trip in addition to Kandalama tank will make more visits to Kandalama tank than those who visit only to the Kandalama tank on their trip. Tourists who spend more time in the Kandalam tank make more visits than those who spent less time in the Kandalam tank. Tourists who are residing close to Kandalama tank make more visits than those who are residing far from Kandalama tank. Therefore, in order to attract more tourists to the Kandalama tank, other places in Dambula area should be developed as tourist spots and more facilities should be developed in Kandalama tank area to enjoy and spend more time.
Keywords: Demand for recreation site; OLS method; Tourism; Travel cost method